Online Sales Application Typical Cake Aceh Based On Android - Veri Ilhadi; Eka Rahma; Sayed Fachrurrazi (Institute of Computer Science (IOCS), 2022)
The development of smartphones makes mobile-based technology considered very effective and efficient for humans, this device has presented various advanced facilities that can help and facilitate every user in doing work and other needs. Among them is marketing a product, including the typical cake in an area. Aceh is one of the destinations for domestic and foreign tourists. Marketing of Aceh's specialty cakes is a fundamental problem experienced by many cake industries. In addition to the cake industry, consumers who want to buy also have obstacles including not knowing the place, price, and number to contact. So to bridge this problem, an application is made that can help the Acehnese cake industry to promote its products more widely throughout Indonesia. This application was built using the SDLC Waterfall, making it easier for researchers to identify problems and design systems according to the needs of the typical Aceh cake sales application. There are several stages, namely requirements analysis, system design, coding, program testing, and program implementation. This Aceh Typical Cake Sales Application for the Province of Aceh was built based on Android with an attractive, effective, and efficient appearance, making it easier for users to run it. After the implementation of this application, the results obtained are that consumers can place orders in real-time, the transaction process is easier and faster, thereby increasing the marketing of Acehnese cakes.